Traffic management inside software-defined data centre networking - Tariq Emad Ali; Ameer Hussein Morad; Mohammed A. Abdala (Institute of Advanced Engineering and Science, 2020)
In recent years, data centre (DC) networks have improved their rapid exchanging abilities. Software-defined networking (SDN) is presented to alternate the impression of conventional networks by segregating the control plane from the SDN data plane. The SDN presented overcomes the limitations of traditional DC networks caused by the rapidly incrementing amounts of apps, websites, data storage needs, etc. Software-defined networking data centres (SDN-DC), based on the open-flow (OF) protocol, are used to achieve superior behaviour for executing traffic load-balancing (LB) jobs. The LB function divides the traffic-flow demands between the end devices to avoid links congestion. In short, SDN is proposed to manage more operative configurations, efficient enhancements and further elasticity to handle massive network schemes. In this paper the opendaylight controller (ODL-CO) with new version OF 1.4 protocol and the ant colony optimization algorithm is proposed to test the performance of the LB function using IPv6 in a SDN-DC network by studying the throughput, data transfer, bandwidth and average delay performance of the networking parameters before and after use of the LB algorithm. As a result, after applying the LB, the throughput, data transfer and bandwidth performance increased, while the average delay decreased.